Valuasi Tumbuhan Akar Kuning (Arcangelisia flava Merr) di Desa Gohong Kabupaten Pulang Pisau Kalimantan Tengah: Valuation of Yellow Root Plant (Arcangelisia flava Merr) in Gohong Village, Pulang Pisau Regency, Central Kalimantan - Yoandri; Sari Mayawati; Nuwa Nuwa; Desy Natalia Koroh; Misrita Misrita (HUTAN TROPIKA, 2022)
The potential of medicinal plants in the forest area of Kalimantan is quite diverse, both those that have been utilized by the community around the region and those that have not been utilized. Gohong Village is a village in Pulang Pisau Regency of Central Kalimantan Province which has an area of ±51,037 ha. The purpose of this study is to analyze the potential the spread and the economic value of yellow root medicinal plants in Gohong Village. The method used in this study is the Purposive Sampling method. The results of the analysis showed that an area of 2 hectares of yellow root plant potential was obtained as much as 2.174415 m3. The density value of yellow roots of 0,1875 or 0,188 for an area of 0.4 hectares there are 75 yellow root plants, and the average measurement plant found yellow root plants as many as 7-8 trees or per hectare, the density value of yellow root plants is 0.47. The frequency of yellow root plants at the research site was 0.8 with the number of plants as many as 75 trees. The spread of yellow roots in Gohong Village is uniform with a morisita index value of 0.8 respondent data in Gohong Village as many as 10 respondents obtained yellow root price data Per 1 Kg is Rp 50,000. Based on the analysis of the availability of yellow roots in the research location is quite significant and able to provide additional income for the community in order to support the economy.